Masculinization of Tilapia (Oreochromis niloticus) Through Immerging Coconut Water with Different Concentrations - Cahyani, Regita; Serdiati, Novalina; Tis'in, Musayyadah; Putra, Aswad Eka (FAPETKAN UNTAD, 2021)
The reproductive nature of female tilapia (Oreochromis niloticus) results in decreased growth of 10-20% per generation which is characterized by small body size, slow growth and rapid maturation of gonads. One effort that can be done is the application of the sex reversal method by increasing the number of male fish through masculinization by utilizing coconut water as a natural ingredient for synthetic hormone replacement because it has relatively complete nutrition, especially potassium (kalium) content which reaches 312 mg/100g. This study aims to determine the effect of using coconut water with different concentrations on the percentage of male tilapia produced. This study was designed in a completely randomized design (CRD) with 4 treatments and 5 replications, treatment A (without coconut water), B (coconut water concentration 25%), C (coconut water concentration 35%) and D (coconut water concentration 45%). Data on the percentage of male sex were analyzed for variance (ANOVA) at the 95% confidence level and further tested by Duncan to see the effect between treatments. The results showed that the treatment of immersion in coconut water with different concentrations had a significant effect (<0.05) on the percentage of male sex of tilapia. The best percentage of male tilapia was immersed in coconut water with a concentration of 35% (treatment C), which was 86.87%.